Obstacles in the pathway to professional life for a Chaldean refugee woman. (1st May 2019) - Lawrence, Jeanette; Merkhaal, Shamiran; Dodds, Agnes
Pathways through university raise obstacles for most students, especially for refugee women. Institutional provisions and social support that facilitate wider access are scarce for high-aspiring refugee students in Australian universities. In this paper, we present a case study of the obstacles to the goals of a teaching career and personal independence expressed by a Chaldean refugee woman. They involved inadequate understanding of her refugee background by students and staff, and the need to prove herself to herself and others, particularly in relation to cultural expectations. Close textual analysis of her comments and reflections revealed an intertwining of university and cultural obstacles. Implications for widening access programmes include the need to recognise the individualised experiences of refugee women whose career pathways involve resistance to cultural expectations, and the need to provide them with appropriate institutional and social support.